Pyrolysis-reforming of cellulose to simultaneously produce hydrogen and heavy organics. (15th February 2023) - Li, Xianglin; Jiang, Yuchen; Zhang, Lijun; Li, Qingyin; Zhang, Shu; Wang, Yi; Hu, Xun
Abstract: The small molecular organics in bio-oil could not be effectively transformed into hydrocarbons with long aliphatic chains or aromatic rings via hydrotreatment, but they could be reformed with steam to generate hydrogen for the hydrotreatment. In this study, the pyrolysis of cellulose coupled with steam reforming of volatiles of small molecular size were performed at 400–600 °C over Ni/Al2 O3 catalyst, which is termed as a pyro-reforming process for simultaneous production of hydrogen and heavy organics for further production of biofuels. The results indicated that the effective reforming of small volatiles became dominant at 600 °C. The coke formed at the low temperatures was mainly polymeric coke of aliphatic nature with low thermal stability, low carbon crystallinity, high reactivity towards oxidation and high hydrophilicity. Increase of temperature to 600 °C reduced the formation of coke (from maximum of 15.0%–12.8%) and suppressed the formation of polymeric coke by promoting gasification of precursors of coke. This enhanced formation of catalytic coke with amorphous morphology as well as defective ring structures. However, homogeneous polymerization of volatiles also took place, forming amorphous coke between catalyst particles. Formation of polymeric coke should be tackled for the successful implementation of pyro-reforming process. Graphical abstract: Image 1 Highlights: Pyro-reforming of cellulose to H2 and heavy organics occurs effectively at 600 °C. Coke formed at 400 °C is polymeric, originating from polymerization of volatiles. More thermally stable catalytic coke while less polymeric coke forms at 600 °C. Ratio of aliphatic coke decreases at higher temperature, but it is not negligible. Homogeneous polymerization of volatile occurs and fills gap of catalyst particles.